A PALAEOMAGNETIC STUDY FROM THE MONGOL-OKHOTSK REGION: ROTATED EARLY CRETACEOUS VOLCANICS AND REMAGNETIZED MESOZOIC SEDIMENTS - Halim N.; Gilder S.; Cogné J.P.; Courtillot V.; Kravchinsky V.; Alexyutin M.; Sorokin A.; Chen Y. (My University, 1998)
We collected 47 sites of Upper Triassic to Middle Jurassic siltstones and sandstones and two sites of Lower Cretaceous andesites in a large basin located south of the Mongol–Okhotsk suture. The suture separates the Siberian craton to the north from the Mongolian and Chinese blocks to the south. Laboratory treatment and analyses identify the same post-folding direction in all rocks. The mean direction (with a corresponding palaeopole at 76.8°N, 152.2°E, A95=4.2°) of the overprint component (N=49 sites) is significantly different at the 95% confidence level from the expected time-averaged Brunhes or present-day field directions. The Lower Cretaceous andesites possess a stable remanent direction at high temperatures that is distinct at 95% confidence limits from the overprint direction. The corresponding pole (58.3°N, 51.0°E, dp/dm = 3.8°/4.6°), based on only fourteen samples, is significantly rotated 78.4°±5.3° counterclockwise and insignificantly displaced 2.7°±3.4° north with respect to the Early Cretaceous reference pole for Siberia. We argue that the rotation is likely tectonic in nature and not due to a chance reading of the palaeosecular variation of the Earth's magnetic field. Both the palaeomagnetic data and the folding patterns we observed in the field suggest that deformation associated with the suture continued after the Early Cretaceous and involved sinistral shear.
Keywords: Mesozoic; Cretaceous; Mesozoic::Cretaceous; Mesozoic; Мезозой::Меловая; Мезозой